2020
DOI: 10.1080/19490976.2019.1701352
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and region-specific effects of sleep fragmentation on gut microbiota and intestinal morphology in Sprague Dawley rats

Abstract: Sleep is a fundamental biological process, that when repeatedly disrupted, can result in severe health consequences. Recent studies suggest that both sleep fragmentation (SF) and dysbiosis of the gut microbiome can lead to metabolic disorders, though the underlying mechanisms are largely unclear. To better understand the consequences of SF, we investigated the effects of acute (6 days) and chronic (6 weeks) SF on rats by examining taxonomic profiles of microbiota in the distal ileum, cecum and proximal colon, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 55 publications
3
22
2
Order By: Relevance
“…Similar microbial changes are observed in sleep fragmentation models at the phylum level; these include increased abundance of species in the Ruminococcaceae family and decreased abundance of species in the Lactobacillaceae family [39,40]. POROYKO et al [39] reported that 4 weeks of sleep fragmentation led to inflammation of the mesenteric adipose tissue in mice, suggesting that microbial translocation and invasion elicited a bacteria-derived inflammatory load.…”
Section: Summary Of Metabolomics Studiesmentioning
confidence: 72%
See 1 more Smart Citation
“…Similar microbial changes are observed in sleep fragmentation models at the phylum level; these include increased abundance of species in the Ruminococcaceae family and decreased abundance of species in the Lactobacillaceae family [39,40]. POROYKO et al [39] reported that 4 weeks of sleep fragmentation led to inflammation of the mesenteric adipose tissue in mice, suggesting that microbial translocation and invasion elicited a bacteria-derived inflammatory load.…”
Section: Summary Of Metabolomics Studiesmentioning
confidence: 72%
“…POROYKO et al [39] reported that 4 weeks of sleep fragmentation led to inflammation of the mesenteric adipose tissue in mice, suggesting that microbial translocation and invasion elicited a bacteria-derived inflammatory load. However, TRIPLETT et al [40] reported that the abundance of intestinal bacteria was significantly changed by prolonged sleep fragmentation, but intestinal permeability and inflammation did not occur. There were differences in sleep fragmentation between these two studies, in terms of the frequency of awakening, which may affect the extent of pathology.…”
Section: Summary Of Metabolomics Studiesmentioning
confidence: 98%
“…Diet, geography, season, and disease have been shown to cause variation in-and potential disruption of-a host's gut flora (Colman et al 2012;King et al 2012;Tang et al 2019). Gut microbes also are subject to spatial and temporal differences throughout the host lifecycle (Llewellyn et al 2016;Triplett et al 2020). Three planorbid snail species exhibited significant differences in gut microbial diversity and abundance at both the individual and species levels (Van Horn et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Sleep disturbance and GM alterationsGM alterations in human and animal models caused by sleep disturbance or related to sleep quality are presented in Table3(top)[71][72][73][74] and Table3(bottom),[75][76][77][78][79][80] respectively. To date, only a few studies explored the effects of sleep impacting on GM in humans, restricting their focus on the association between specific bacterial taxa and sleep quality based on Pittsburgh sleep quality index (PSQI) or sleep physiology.…”
mentioning
confidence: 99%